Ligation of Innominate Artery and Axillo-axillary Crossover Bypass for Innominate Artery Stenosis with Irregular Atheroma - Shichijo, Takeshi; Kato, Gentaro; Hayashida, Tomohiro; Ogawa, Tatsuya; Yamamoto, Shu (Japanese Journal of Vascular Surgery, 2020)
An 84-year-old man developed right cerebral infarction recently twice a year. Enhanced computed tomography revealed innominate artery stenosis with irregular atheroma and diameter of innominate artery was expanded to 17 mm. The atheroma was considered to be the cause of cerebral infarction, and the patient was referred to our hospital for treatment. Endovascular therapy was thougut to be inadequate due to vascular diameter and the difficulty of brain protection. The operation was performed by direct ligation of innominate artery and revascularization by axillo-axillary artery crossover bypass. The postoperative course was uneventful, and the patient was discharged on 6th postoprerative day. One year after the operation, no new symptoms have been observed. The ligation of innominate artery and axillo-axillary artery crossover bypass were effective and less invasive strategy for innominate artery stenosis with irregular atheroma.